Penerapan Model Pembelajaran TGT Untuk Meningkatkan Prestasi Belajar dan Perilaku Toleransi Siswa Kelas IV SD - Fitria Komalasari; Osa Juarsa (Universitas Bengkulu, 2023)
This study aims to improve student achievement and tolerance behavior in Thematic learning class IV SDN 17 Bengkulu City by applying the Cooperative learning model type Teams Games Tournament (TGT). The observation data analysis technique uses the formula of the average score, the highest score, the lowest score, the difference in score and the range of values ​​for each criterion. Test data were analyzed using the formula of the average grade and the percentage of classical learning. The average results of the application of the type 1 cooperative learning model Teams Games Tournament obtained 2.44 and cycle II increased 3.68. The average results of the tolerance behavior of students in the first cycle were 7.92 with sufficient categories and the second cycle obtained 13.58 with very good categories. Learning achievements of the first cycle in social studies subjects average grade of 62.4, in the second cycle the average value of the class was 82. Indonesian subjects in the first cycle average grade of 67.2, in the second cycle the average value average class of 80.4. PPKn subjects in the first cycle the average value of the class is 69.2, in the second cycle the average value of the class is 78.88. Thus the application of cooperative learning model type Teams Games Tournament (TGT) can improve student achievement and tolerance behavior in Thematic learning in class IV SDN 17 Bengkulu City.